2016
DOI: 10.1128/jvi.00954-16
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the PA-X C-Terminal Domain of Influenza A Virus in Its Subcellular Localization and Shutoff Activity

Abstract: PA-X is a recently identified influenza virus protein that is composed of the PA N-terminal 191 amino acids and unique C-terminal 41 or 61 residues. We and others showed that PA-X has a strong ability to suppress host protein synthesis via host mRNA decay, which is mediated by endonuclease activity in its N-terminal domain (B. -12). However, the mechanism of host mRNA degradation, especially where and how PA-X targets mRNAs, has not been analyzed. In this study, we determined the localization of PA-X and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
115
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(129 citation statements)
references
References 34 publications
14
115
0
Order By: Relevance
“…4 and 8), which is consistent with previous findings (Gao et al, 2015a). However, two recent studies described that the first 15aa in the C-terminal region of PA-X are sufficient for maximum shutoff activity, while the addition of 20 aa of C-terminal end is not critical to shutoff activity of PA-X (Hayashi et al, 2016; Oishi, Yamayoshi, and Kawaoka, 2015). The reason for the different observations in shutoff activities of truncated PA-X between these studies could be due to differences of PA-X expression systems used, resulting in different protein expression levels, thereby showing a difference of the host shutoff activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 and 8), which is consistent with previous findings (Gao et al, 2015a). However, two recent studies described that the first 15aa in the C-terminal region of PA-X are sufficient for maximum shutoff activity, while the addition of 20 aa of C-terminal end is not critical to shutoff activity of PA-X (Hayashi et al, 2016; Oishi, Yamayoshi, and Kawaoka, 2015). The reason for the different observations in shutoff activities of truncated PA-X between these studies could be due to differences of PA-X expression systems used, resulting in different protein expression levels, thereby showing a difference of the host shutoff activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the different observations in shutoff activities of truncated PA-X between these studies could be due to differences of PA-X expression systems used, resulting in different protein expression levels, thereby showing a difference of the host shutoff activity. Because the whole PA expression plasmid was used in our study and the former studies, which could generate full-length or truncated PA-X by ribosomal frameshifting (Gao et al , 2015a), while PA-X expression plasmids were used in latter studies (Gao et al, 2015a; Hayashi et al, 2016; Oishi, Yamayoshi, and Kawaoka, 2015). Comprehensive phylogenetic and evolutionary analysis revealed that truncated PA-X appears in particular hosts such as dogs and swine which indicates species specificity of PA-X protein (Shi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that multiple mechanisms are related to host shutoff in IAV-infected cells. However, recent studies have focused on the following three main mechanisms of global inhibition of host protein expression by IAV infection: (1) blockade of cellular mRNA processing and nuclear export by NS1 [16][17][18][19]; (2) degradation of host RNA Pol II by the viral RNA-dependent RNA polymerase RdRp complex (RdRP) [20][21][22]; and (3) wide-spread host mRNA degradation by the PA-X protein [11,[23][24][25][26][27][28][29][30][31]. In this review, we focus mainly on the shutoff activity of PA-X protein.…”
Section: Global Host-shutoff Activity By the Pa-x Proteinmentioning
confidence: 99%
“…Recombinant A/California/04/2009 (H1N1) virus was rescued previously by a 12-plasmid rescue system (Hayashi et al, 2016) and propagated in eggs. A/Victoria/361/2011 (H3N2) virus was kindly provided by Dr. David Topham (University of Rochester) and propagated in MDCK cells in DMEM supplemented with 0.15% bovine serum albumin (BSA) and acetylated trypsin at 2 μg/ml.…”
Section: Methodsmentioning
confidence: 99%